Activismo teatral durante la última dictadura argentina: Apuntes sobre el Taller de Investigaciones Teatrales - Longoni, Ana (2014)
This article is part of an ongoing research on the Taller de Investigaciones Teatrales (1977-1982), one of the collectives of artistic activism that emerged arose in Argentina during the harshest years of the last dictatorship. In their different proposals (theater, film, music, and literature workshops, production of festivals, publication of manifestos and fanzines, discussion group on the situation of women, etc.) they brought together hundreds of young people for whom political activism was prohibited, promoting artistic experimentation as a radical method not just for surviving: for living effervescentfrenzied exalted experiences of freedom, self-assurance, and provocation that challenged the established normalcy.